Experimental observation and micromagnetic understanding of the current-induced magnetization reversal process in Ta/Pt/[Co/Ni]nCo/Ta multilayers. (2nd September 2021) - Zeng, Xiaoxue; Jia, Qi; Sun, Shuling; Guo, Yonghai; Wang, Bo; Wang, Ying; Cao, Jiangwei
Abstract: We investigate a current-induced magnetization reversal process mediated by spin–orbit torque (SOT) in Ta/Pt/(Co/Ni) n Co/Ta multilayers experimentally and by micromagnetic simulation. Experimental results show that the current-induced magnetization reversal in these samples is completed by nucleation and subsequent domain wall (DW) propagation. For samples with a small number ( n ) of Co/Ni bi-layers, which show strong Dzyaloshinskii–Moriya interaction (DMI), when the in-plane magnetic field ( Hx ) is weaker than a critical value, the tilted DWs form in the final stabilized state, corresponding to a partial magnetization reversal. Since Hx is close to the DMI effective field, the domains expand asymmetrically to semicircular areas, finally resulting in complete magnetization reversal. For the sample with large n and weak DMI, the reversed domains grow obliquely along a special orientation, which varies with the magnitude of Hx . These experimental phenomena are well reproduced by micromagnetic simulation after taking into account the SOT effect and the DMI-modulated magnetic moment distribution in the DW. The agreement betweenexperimental observation and micromagnetic simulation suggests that the current-induced magnetization reversal process in the Ta/Pt/[Co/Ni] n Co/Ta system can be well understood within the framework of SOT and the DMI scenario.